Self-locking Fe-based shape memory couplers: Insights into SME and interface contact mechanics - Ali Jafarabadi; Maryam Mohri; Elyas Ghafoori; Eleni Chatzi; Christian Leinenbach; Christoph Czaderski (Materials & Design)
Fe-based Shape memory alloys (Fe-SMAs) have been extensively utilized in a variety of innovative engineering applications. Notably, Fe-based shape memory couplers present an alternative to welded and machined mechanical joints, offering advantages such as self-locking assembly and reduction of stress concentrations. However, further characterization in terms of multiaxial shape memory effect (SME) and, geometrical as well as implementation parameters is crucial for the purpose of reliable strength evaluation. While significant progress has been made toward understanding the uniaxial characteristics of the SME—driven by major developments and widespread use of such materials—the behaviour of Fe-SMAs under complex loading conditions, such as those involving multiaxial phase transformations, remains less well understood. During the pre-straining process of Fe-SMA tubes, non-uniform biaxial stress-state leads to a complex stress-induced martensite formation, posing challenges in the assessment of SME. Nonetheless, it is feasible to interpret the overall SME performance based on the resultant pressure exerted by the Fe-SMA tube on a substance, thereby limiting its free recovery. This study explores the impact of heat-treatment, pre-straining level, activation temperature and wall-thickness on interface contact pressure, providing insights into the gripping capacity in Fe-SMA tubes, which is crucial for evaluating the strength of shape memory joints. Via coupling of analytical models with results extracted from an experimental campaign, the resultant pressure at the interface throughout the course of activation is quantified, aiding to assess the SME performance. The obtained results highlight the complex interaction between post-processing and structural parameters, shedding light on the design and implementation of Fe-SMA coupling components with enhanced SME performance.